CONSERVED SEQUENCE IN THE AGGRECAN INTERGLOBULAR DOMAIN MODULATES CLEAVAGE BY ADAMTS-4 AND ADAMTS-5 - Miwa, Hazuki E (2008)
BACKGROUND: Cleavage of aggrecan by ADAMTS proteinases at specific sites within highly conserved regions may be important to normal physiological enzyme functions, as well as pathological degradation. METHODS: To examine ADAMTS selectivity, we assayed ADAMTS-4 and -5 cleavage of recombinant bovine aggrecan mutated at amino acids N-terminal or C-terminal to the interglobular domain cleavage site. RESULTS: Mutations of conserved amino acids from P18 to P12 to increase hydrophilicity resulted in ADAMTS-4 cleavage inhibition. Mutation of Thr, but not Asn within the conserved N-glycosylation motif Asn-Ile-Thr from P6 to P4 enhanced cleavage. Mutation of conserved Thr residues from P22 to P17 to increase hydrophobicity enhanced ADAMTS-4 cleavage. A P4′ Ser377Gln mutant inhibited cleavage by ADAMTS-4 and -5, while a neutral Ser377Ala mutant and species mimicking mutants Ser377Thr, Ser377Asn, and Arg375Leu were cleaved normally by ADAMTS-4. The Ser377Thr mutant, however, was resistant to cleavage by ADAMTS-5. CONCLUSION: We have identified multiple conserved amino acids within regions N- and C-terminal to the site of scission that may influence enzyme-substrate recognition, and may interact with exosites on ADAMTS-4 and ADAMTS-5. GENERAL SIGNIFICANCE: Inhibition of the binding of ADAMTS-4 and ADAMTS-5 exosites to aggrecan should be explored as a therapeutic intervention for osteoarthritis.